PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN DIVIDEN, LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Herman Sjahruddin; Nur Asa Nikmatul Jannah (Niagawan, 2022)
This study aims to examine the effect of firm size, profitability, dividend policy, leverage, and liquidity on firm value in the basic industry  and chemical sub-sectors of the cement industry listed on the Indonesia Stock Exchange for the 2016-2019 period. This study uses a quantitative paradigm by utilizing three issuer's quarterly financial statements which were analyzed using linear regression. The results of the analysis provide evidence that leverage and liquidity have a significant negative effect on firm value, whereas firm size, profitability and dividend policy contribute positively but cannot increase the firm values